Justice for Nature: Integrating Environmental Concerns into Legal Systems for Adequate Environmental Protection - Nur Insani; Suud Sarim Karimullah (Puslitbang Hukum dan Peradilan Mahkamah Agung RI, 2023)
This research explores the importance of integrating environmental interests into the legal system, advocating justice for nature, and realizing a greener and more sustainable world. Based on a comprehensive literature review and critical analysis of relevant sources, this study identifies the key elements needed, namely effective environmental law enforcement mechanisms, active participation of stakeholders, and synergies that link community participation with environmental law awareness. A reliable law enforcement mechanism is a key pillar in environmental protection, involving a fair and efficient judicial process supported by robust law enforcement agencies and adequate sanctions. Stakeholders, including governments, law enforcement agencies, civil society, and the private sector, play a central role in policy formation, implementation monitoring, participation in decision-making, environmental advocacy, and increased awareness of environmental law. The combination of active community participation and environmental law awareness has a positive impact on maintaining environmental sustainability, with community participation covering environmental management, engaging in decision-making, and community empowerment. In contrast, environmental law awareness strengthens law enforcement, understands environmental rights and obligations, and encourages sustainable behavioral change. Thus, this comprehensive integration paves the way to a world in which the interests of nature are heard and protected, creating a more equitable and sustainable global ecosystem.